Transformational Leadership and Organizational Commitment: Key Drivers of Citizenship Behavior Across Various Climates - Martoyo, Martoyo; Amara, Dinda (Institut Agama Islam Negeri Lhokseumawe, 2024)
This study examines the intricate relationships among Transformational Leadership, Organizational Climate, Organizational Commitment, and Organizational Citizenship Behavior (OCB) within the school context in Indonesia. Utilizing a sample of 76 teachers from Public Senior High School 1 Metro, data were collected and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through the Smart-PLS analytical tool. The results indicate that Transformational Leadership significantly influences both Organizational Climate and Organizational Commitment directly. However, it does not exhibit a significant direct effect on OCB. Additionally, Organizational Climate neither directly impacts OCB nor mediates the relationship between Transformational Leadership and OCB. In contrast, Organizational Commitment acts as a significant indirect mediator between Transformational Leadership and OCB. Future research should focus on enhancing OCB across various organizational types, particularly schools throughout Indonesia, on fostering behavior among teachers that voluntarily and collectively support organizational goals.